Proceedings of the 35th International ACM SIGIR Conference on Research and Development in Information Retrieval 2012
DOI: 10.1145/2348283.2348310
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive diversification of recommendation results via latent factor portfolio

Abstract: This paper studies result diversification in collaborative filtering. We argue that the diversification level in a recommendation list should be adapted to the target users' individual situations and needs. Different users may have different ranges of interests -the preference of a highly focused user might include only few topics, whereas that of the user with broad interests may encompass a wide range of topics. Thus, the recommended items should be diversified according to the interest range of the target u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 33 publications
0
50
0
Order By: Relevance
“…Ishikawa et al [33] exploited information diffusion theory to recommend novel technical articles to interested users; additionally, Shi et al [66] used portfolio theory from the field of economics to tune recommendations (50), [16](288), [20] (382) between risk-taking and risk-aversion.…”
Section: Other Algorithmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ishikawa et al [33] exploited information diffusion theory to recommend novel technical articles to interested users; additionally, Shi et al [66] used portfolio theory from the field of economics to tune recommendations (50), [16](288), [20] (382) between risk-taking and risk-aversion.…”
Section: Other Algorithmsmentioning
confidence: 99%
“…Portfolio theory provides a framework by which to tune the degree of risk inherent in the retrieved information. The portfolio concept introduced by Wang et al was extended to the study of recommendations by Shi et al [66].…”
Section: Relation To Other Information-retrieval Domainsmentioning
confidence: 99%
“…A variation using a covariance matrix created on explicit item-aspect assignments was proposed and evaluated in [9]. Another adaptation of the Mean-Variance framework has been proposed in [10] for latent factor models by employing variance of learned user latent factors to address users' individual situations.…”
Section: Modelling and Evaluating Diversity Of Recommendationsmentioning
confidence: 99%
“…they are independent of the user's preferences. A user-dependent covariance has been proposed in [10], however this is in the context of latent factorisation models.…”
Section: Intent-aware Portfolio Diversificationmentioning
confidence: 99%
“…Previous studies have found that users vary in terms of the degree of diversification that is optimal for them, and that this can be deduced from their previous rating behavior (see e.g., [13,21]). Users also vary in terms of personality traits that are fixed, such as the Big Five [12].…”
Section: User Diversitymentioning
confidence: 99%